Study on Relationship between Cigarette Smoking and Hemoglobin Levels in a Healthy Adult Bangladeshi Male Population (Community Based Medical Journal, 2026)
A cross-sectional, comparative study was conducted in the Outpatient Department (OPD) of Mymensingh Medical College Hospital, Mymensingh, Bangladesh, from July 2014 to June 2015, to observe the relationship between cigarette smoking and hemoglobin levels in healthy adult male population. We studied on a total of 150 participants, comprising 50 non-smokers (group-I) and 100 smokers (group-IIA with 5-10 years duration of smoking and group-IIB >10 years duration of smoking). Hemoglobin concentration was measured using the cyanmethemoglobin method. A questionnaire including data was completed in all cases. The survey data were checked, coded, and analyzed. Hemoglobin levels were found increased with the duration of smoking in both study groups, i.e., group-IIA and group-IIB, as compared with the control group (nonsmokers, group-I) (p